School Strategies to Utilize the Ecotourism Potency of Songgoriti and Cangar of Batu City Tourisms as Learning Sources in High School - Moch. Agus Krisno Budiyanto; Tien Aminah; H. Husamah (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2020)
School strategies and perceptions of the school principals in utilizing the ecotourism potency is one of important things-which is used as an effort to support the improvement of the quality of learning, not much has been revealed yet. This study aimed at analyzing the school strategies and perspective of school principal in utilizing the ecotourism potency of Songgoroti and Cangar-Batu City tourisms as learning sources in High School. This study used a qualitative approach. Phenomenology was used as design of study. Teachers, school principals, and students of SMAN 3 Malang, SMA Sholahuddin Malang, and MAN 1 Malang were the informants of study. Sampling technique used was purposive sampling. Data collection methods used in this study were in-depth interview and questionnaires. The data of study obtained were analyzed by means of content analysis referred to Interactive Models Miles, Huberman and Saldana, and those were presented in a descriptive description. The results of study indicated that the school strategies in utilizing the ecotourism potency covered up 1) the analysis strategy of ecotourism potency as effective learning sources for High School in an effort to determine learning place, Â in which it consisted of two strategies, namely (a) Student- Teacher Centered Strategy and (b) Teacher -Student Centered Strategy; 2) The planning strategy in utilizing the ecotourism potency as effective learning sources consisted of three strategies, namely (a) initiator strategy, (b) planning policy-making process strategy, and (c) planning implementation strategy; and 3) The implementation strategy in utilizing the ecotourism potency consisted of two strategies, namely (a) Collaborative/Resource sharing Strategy, dan (b) Semi-collaborative Strategy. The perceptions of school principals in utilizing the ecotourism potency were that the school principals were very supportive, both through direct statements and through policies made. It can be concluded that there are various strategies to utilize the ecotourism potency of learning sources in High School. The principals reinforce the utilization effort through direct statements and policies that are made. In the future, a study is needed on the implementation of the utilization of ecotourism potency in learning.